2021
DOI: 10.3390/s21134509
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Structures with Surface Nanoscale Interfaces Formed by Au, Fe2O3, or Cu2O Modifier Nanoparticles: Characterization and Gas Sensing Properties

Abstract: Zinc oxide rod structures are synthetized and subsequently modified with Au, Fe2O3, or Cu2O to form nanoscale interfaces at the rod surface. X-ray photoelectron spectroscopy corroborates the presence of Fe in the form of oxide—Fe2O3; Cu in the form of two oxides—CuO and Cu2O, with the major presence of Cu2O; and Au in three oxidation states—Au3+, Au+, and Au0, with the content of metallic Au being the highest among the other states. These structures are tested towards nitrogen dioxide, ethanol, acetone, carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 60 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…A brief study of the hysteresis graph in Figure g showed that the device responds to NO at a concentration as low as 0.5 ppm. These results showcase the exceptional gas sensing property of green synthesized CuO/ZnO heterostructures at low operating temperatures and low analyte gas concentrations, unlike most chemically synthesized SMO that are responsive only at higher operating temperatures and high concentrations of analyte gas. Another notable observation was that, that the increase in temperature (50 °C) did not have any adverse effects on the shape and quality of the bioplastic substrate. This means that the substrate could be used at operating temperatures slightly higher than RT.…”
Section: Resultsmentioning
confidence: 70%
“…A brief study of the hysteresis graph in Figure g showed that the device responds to NO at a concentration as low as 0.5 ppm. These results showcase the exceptional gas sensing property of green synthesized CuO/ZnO heterostructures at low operating temperatures and low analyte gas concentrations, unlike most chemically synthesized SMO that are responsive only at higher operating temperatures and high concentrations of analyte gas. Another notable observation was that, that the increase in temperature (50 °C) did not have any adverse effects on the shape and quality of the bioplastic substrate. This means that the substrate could be used at operating temperatures slightly higher than RT.…”
Section: Resultsmentioning
confidence: 70%
“…The Au‐modified ZnO films exhibited remarkable response and sensitivity, particularly towards NO 2 and ethanol, with a 47‐fold more robust response to 10 ppm NO 2 than the unmodified ZnO structures with 39.96 % ppm −1 sensitivity and 26 parts per billion (ppb) LOD. The catalytic nature of the Au nanoparticles, the gas‐sensing mechanism induced by the nano‐interfaces between ZnO and Au, and the presence of oxygen vacancies are all aspects that contributed to these results [150] …”
Section: Development Of Materials By Aacvd For Carious Applicationsmentioning
confidence: 98%
“…The catalytic nature of the Au nanoparticles, the gas-sensing mechanism induced by the nano-interfaces between ZnO and Au, and the presence of oxygen vacancies are all aspects that contributed to these results. [150] 4.8. Super-Hydrophobic Thin Films Superhydrophobic surfaces are an exciting research area that has established their worth in various technological fields of aerospace, automotive, construction, medical, and optical.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Furthermore, even at a lower ethanol concentration of 10 ppm, the composite material exhibited a good response value of 63 and fast response/recovery times of 4 s/5 s. However, it is worth noting that without Au functionalization, the sensing performance of single composite n-n MOS materials does not seem to be ideal. Tomic et al 172 conducted experimental studies on Au/ZnO, Fe 2 O 3 /ZnO, Cu 2 O/ZnO, and pure ZnO samples to investigate the effect of modifiers on ZnO. Sensing detection showed that Au/ZnO exhibited the best sensing performance, while the pure ZnO sample exhibited the worst performance.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%